The economics of integrated tick and tick-borne disease control on commercial farms in Zimbabwe - Perry, Brian D.; Chamboko, Tafireyi; Mahan, S.M.; Medley, G.F.; Minjauw, B.; O'Callaghan, C.J.; Peter, T.F. (1998)
The authors highlight the reliance on repeated natural infections by tickborne pathogens to maintain immunity in immunized herds. That incidence of clinical heartwater in cattle, caused by Cowdria ruminantium, is low while intensive acaricide use interrupts transmission of pathogens. Evidence is presented demonstrating that integrated control based on the establishment of endemic stability by vaccination or natural challenge is not only biologically robust, but is also of considerable economic advantage over intensive dipping. In a survey conducted in 1995-96 of 37 predominantly beef farms in Harare, Zimbabwe, mortality was higher in cattle treated >30 times with acaricide than in those with a less intensive programme. It is concluded that a more strategic programme of acaricide application is economically superior to the intensive programme.